Observational Study of Effects of Saroglitazar on Glycaemic and Lipid Parameters on Indian Patients with Type 2 Diabetes - Chatterjee, Sanjay (Sci Rep, 2015)
Cardiovascular risk reduction is an important issue in the management of patients with Type 2 diabetes mellitus. Peroxisome proliferator activated receptor (PPAR) agonists favourably influence glycaemic and lipid parameters in patients with Type 2 diabetes and a dual PPAR agonist is expected to have favourable effect on both parameters. In this study we have analyzed the effect of Saroglitazar, a novel dual PPAR alpha & gamma agonist, on glycaemic and lipid parameters in Indian patients with Type 2 diabetes. After a mean follow-up period of 14 weeks in 34 patients, treatment with Saroglitazar, in a dose of 4 mg daily, resulted in significant improvement in both glycaemic and lipid parameters. There were significant mean reductions of fasting plasma glucose (36.71 mg/dl; p = 0.0007), post-prandial plasma glucose (66.29 mg/dl; p = 0.0005), glycosylated haemoglobin (1.13%; p < 0.0001), total cholesterol (48.16 mg/dl; p < 0.0001), low- density lipoprotein cholesterol (24.04 mg/dl; p = 0.0048), triglyceride (192.78 mg/dl; p = 0.0001), non-high density lipoprotein cholesterol (48.72 mg/dl; p < 0.0001) and the ratio of triglyceride and high density lipoprotein cholesterol (5.30; p = 0.0006). There was no significant change in body weight, blood pressure, high-density lipoprotein cholesterol and serum creatinine.